Lysosomal Acid Lipase: Can it be a New Non-Invasive Serum Biomarker of Cryptogenic Liver Fibrosis and Cirrhosis? - Gravito-Soares, Marta (2019)
Introduction and aim. The association between lysosomal acid lipase (LAL) activity and liver steatosis or fibrosis is poorly st ud- ied. The aim of our study was to determine the predictive power of LAL for cryptogenic liver steatosis and cryptogenic significant fi- brosis/cirrhosis. Material and methods.Material and methods.Material and methods.Material and methods.Material and methods. Cross-sectional observational study of 101 adult patients with unexplained elevated liver enzymes/hepatomegaly with or without dyslipidemia submitted to the determination of LAL activity and LIPA gene (E8SJM- C.894GoA) mutation. Seventy-one patients underwent liver biopsy or FibroScan®. Patients with an identifiable liver dysfunction cause and well-stablished NAFLD/NASH risk factors were excluded. Predictors for liver steatosis, significant fibrosis (t F2) or cir- rhosis (F4) were evaluated. Results.Results.Results.Results.Results. Liver steatosis and fibrosis were mainly assessed by liver biopsy (74.6%; n = 53). Steatosis was present in 62.0% (n = 44), significant fibrosis in 47.9% (n = 34) and cirrhosis in 39.4% (n = 28). The median LAL was 0.36 (0.21-0.46)nmol/spot/h (vs. 0.29 (0.20-0.47); p = 0.558) for liver steatosis, 0.22 (0.11-0.29) nmol/spot/h (vs. 0.40 (0.34-0.51); p < 0.001) for significant fibrosis and 0.21 (0.11-0.27) nmol/spot/h (vs. 0.40 (0.32-0.52); p < 0.001) for cirrhosis. No LIPA gene mutations were found. LAL activity was the strongest predictor of significant fibrosis (AUROC: 0.833; p < 0.001) with a cut-off of 0.265(sensi- tivity: 85.9%; specificity: 75.0%) and cirrhosis (AUROC: 0.859; p < 0.001) with a cut-off of 0.235 (sensitivity: 86.2%; specifi city: 75.0%), being higher than FIB4, GUCI or APRI. However, LAL activity was not associated with liver steatosis (AUROC: 0.536; p = 0.558). Conclusion.Conclusion.Conclusion.Conclusion.Conclusion. LAL activity can be considered a non-invasive new marker of cryptogenic liver fibrosis with higher accuracy than other known biomarkers. LAL activity < 0.265 nmol/spot/h was strongly associated with cryptogenic significant fibrosis and < 0.235 nmol/spot/h with cryptogenic cirrhosis. LAL activity was not associated with cryptogenic liver steatosis